Evolution of sexual dimorphism and polychromatism in a lineage of tiger moths (Lepidoptera: Erebidae): advancing knowledge of a taxonomically chaotic group. (29th April 2021) - Moraes, Simeão de Souza; Murillo‐Ramos, Leidys; Duarte, Marcelo
Abstract: Pericopina is divided into 36 genera, with the greatest diversity recorded in the Neotropics. Studies on the taxonomy and systematics of pericopines are scarce, and one of the few phylogenetic hypotheses available in the literature places some Afro‐Indo‐Malayan lineages among the Neotropical representatives. Through a survey of adult morphological characters, we analyzed the phylogenetic relationships in Pericopina including Nyctemera and other Afro‐Indo‐Malayan genera as putative members of this subtribe. Additionally, we tested the monophyly of Dysschema, a key genus to understanding the evolutionary patterns of the extreme sexual dimorphism and polychromatism in Pericopina. Our cladistic analysis, based on 162 morphological characters, suggests that Pericopina is a polyphyletic group. Xenosoma is the only genus among the Neotropical pericopines related to the Afro‐Indo‐Malayan species; Scearctia is closely related to Lithosiini, and Pteroodes shows morphological similarities with Phaegopterina. Additionally, Seileria is a new junior subjective synonym of Thyrgis . The monophyly of Dysschema is supported only if the monotypic genera Myserla and Are are included. These are herein designated new synonyms of Dysschema . Our findings suggest that intersexual polychromatism and intersexual polymorphism for wing characters have arisen multiple times in the evolutionary history of Pericopina. Intersexual polychromatism is also widely distributed within Dysschema, perhaps representing a derived feature with multiple origins in the genus.